Contribution of managerial capabilities and achievements in industrial work practices to the interest in automotive entrepreneurship - Al Fajri; Slamet Priyanto2; Nurcholish Arifin Handoyono (Jurnal Taman Vokasi, 2019)
The purpose of the research is to know how much contribution of managerial ability and industrial work practice achievements either partially or simultaneously to the interest in automotive entrepreneurship. The type of research is ex-post facto research with a population of 67 students class XII of the Automotive Engineering Expertise Program. The number of samples is determined with Harry King nomogram’s as many as 63 students and taken by simple random sampling technique. The instrument of data collection use questionnaire for managerial ability and interest in automotive entrepreneurship, and documentation for the industrial work practice achievements. The data analysis technique uses descriptive statistics; analysis prerequisite test use normality, linearity, and multicollinearity tests; and hypothesis test use partial correlation, multiple correlations, and F-test with multiple regression analysis. The results showed that: (1) managerial ability and industrial work practice achievements simultaneously contributed positively and significantly by 58.1% to the interest in automotive entrepreneurship; (2) managerial ability contributed positively and significantly by 54.3% to the interest in automotive entrepreneurship; and industrial work practice achievements contributed positively but not significantly by 1.3% to the interest in automotive entrepreneurship.